The main directions of socio-educational support of elderly people in Ukraine - Tetiana Kolenichenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article analyzes the concept of "old age" and proposes the author’s definition of this concept. The results of the pilot phase of the research as for the identification of the elderly people’s needs have been presented; the estimation of identified needs and levels which will meet the identified needs of the elderly person: micro (community); mezo (local level); macro (national level) have been grounded. The content of the main directions of the elderly person’s support in social transformation has been shown and disclosed.